2017
DOI: 10.1111/jopr.12580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Unfilled Space Size of the Abutment Screw Access Hole on the Extruded Excess Cement and Retention of Single Implant Zirconia Crowns

Abstract: The amount of extruded excess cement was reduced by more than half when a 2-mm space of the screw access hole was left unfilled in comparison to the nonspaced counterpart. The retention of zirconia copings was not affected by the reported technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although cement-retained crowns are favored by dentists, their shortcomings are obvious: when they need to be retrieved, the crowns have to be broken, 1 , 10 , 19 excess cement residue underneath the gingiva is difficult or impossible to avoid, 20 , 21 and such excess cement may lead to peri-implant disease. 22 Therefore, previous studies have reported various methods for reducing residual cement around the abutment margin of cement-retained implant crowns, such as making venting holes, 23–27 using polytetrafluoroethylene tape 28 , 29 or a rubber dam, 30 reducing the amount of cement applied, 31 modifying the shape of the abutment 32 or increasing the unfilled space of the abutment, 33 , 34 using the pre-seating technique 19 , 35 by accustomed abutment duplication, avoiding placing the crowns’ restorative margin into a deep place underneath the gingiva 36 and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Although cement-retained crowns are favored by dentists, their shortcomings are obvious: when they need to be retrieved, the crowns have to be broken, 1 , 10 , 19 excess cement residue underneath the gingiva is difficult or impossible to avoid, 20 , 21 and such excess cement may lead to peri-implant disease. 22 Therefore, previous studies have reported various methods for reducing residual cement around the abutment margin of cement-retained implant crowns, such as making venting holes, 23–27 using polytetrafluoroethylene tape 28 , 29 or a rubber dam, 30 reducing the amount of cement applied, 31 modifying the shape of the abutment 32 or increasing the unfilled space of the abutment, 33 , 34 using the pre-seating technique 19 , 35 by accustomed abutment duplication, avoiding placing the crowns’ restorative margin into a deep place underneath the gingiva 36 and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of REC may increase suppuration, bleeding on probing and possibly peri‐implant attachment loss 34 . To prevent these problems caused by excess cement, various methods have been investigated, as follows: leaving different space sizes of the abutment screw‐access channel (SAC), 19,20 creating a vent hole on the crown, 21,22 reducing the amount of cement loaded into the crown, 23 using a rubber dam or polytetrafluoroethylene tape, 24,25 and using a custom‐made duplicate or practice abutment 26…”
Section: Discussionmentioning
confidence: 99%
“…While cement‐retained restorations are suspected of causing more biological complications, 15,16 screw‐retained fixed prostheses appear to be more prone to technical failures 17,18 . Many methods have been investigated to prevent the problems caused by REC, 19–26 such as creating a vent hole on the crown surface 21,22 …”
mentioning
confidence: 99%
“…Although cement-retained implant crowns are favored by dentists for their low cost and easy handling, their disadvantage is obvious: it is difficult and sometimes impossible to avoid excessive subgingival cement residue, which can lead to peri-implant disease [ 11 , 18 ]. Due to the deleterious effect of the extruded cement residue, attempts have been made to find methods to eliminate these drawbacks, such as opening holes of different diameters on the crown [ 19 , 20 ], increasing the unfilled space of the abutment screw access hole [ 19 ], loading a precise amount of cement on the crown [ 21 ], placing the crown’s margin supragingivally [ 22 ], using polytetrafluoroethylene tape or a rubber dam as a barrier [ 23 , 24 ], and applying customized abutment analogs prior to final cementing to obtain a customized cement film thickness [ 25 ]. Of all these methods, opening a vent hole on the crown is the easiest, and it requires no additional time or costs, making it practical and worthy of clinical application [ 26 ].…”
Section: Discussionmentioning
confidence: 99%